EKSPLORASI PERSEPSI PASIEN RSUP DR SARDJITO TERHADAP KETERAMPILAN MEDIS DOKTER MUDA FAKULTAS KEDOKTERAN UNIVERSITAS GADJAH MADA - , MUHAMMAD TSANI ARSYAD, Dr. Widyandana, MHPE, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Medical students went through preclinical and clinical phase. Learning process in Skills Laboratory expected to make medical students become more skilled and ready to face the clerkship phase in hospital. Patients as health care service consumer who interacted directly with clerkship students have perceptions about their clinical skills that performed in the hospital. Objective: To understand patients perception and suggestions about medical skills of clerkship students in hospital. Method: Twenty eight patients (6 patients from Pediatric ward, 7 patients from surgery ward, 8 patients from Internal Medicine ward, and 7 patients from Obstetric and Gynecology ward) were required to fulfill a questionnaire consists of open and structured questions about clerkship students medical skills. The data was analyzed manually and coded by 2 coders using inductive content analysis method based on guideline from Ello and Kyngas (2008). Results: in patients perception, over all clerkship students were ready to be a health care provider. Eighty nine percent patients said that clerkship students have good communication skills. Seventy two percent patients couldnât assess physical examination skills of clerkship students. Ninety three percent patients couldnât assess medical procedural skills of clerkship students. Sixty eight percent patients couldnât assess clerkship studentsâ medical knowledge. And twelve and a half percent patients suggested that clerkship studentsâ medical skills will be improved if they learn more and become more proactive while undergoing clinical phase. Conclusion: Based on patients perception, clerkship students were ready to be a health care provider. Patients said that clerkship students did well in communication. But because of patientsâ lack of knowledge in clerkship studentsâ tasks and competence, patients couldnât assess clerkship studentsâ physical examination skills, procedural skills, and studentsâ medical knowledge optimally. Patients suggested that clerkship patientsâ skills will be improved by learning more and becoming more proactive while undergoing clinical phase.